2008
DOI: 10.32725/jab.2008.003
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic effect of Cardiospermum halicacabum Linn. leaf extract on STZ-induced diabetic rats

Abstract: The present study was designed to investigate the antihyperglycaemic effect of ethanolic extract of Cardiospermum halicacabum Linn. (Sapindaceae) leaves on normal and streptozotocin (STZ) diabetic rats. Diabetes was induced into male albino Wistar rats by intraperitonial administration of STZ. The Cardiospermum halicacabum leaf extract (CHE) was administered orally at three different doses to normal and STZ-diabetic rats for 45 days. The diabetic rats showed an increase in levels of blood glucose and glycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
(13 reference statements)
0
23
0
Order By: Relevance
“…The loss of body weight after administration of STZ may be due to the loss of degradation of structural proteins [32]. The administration of EESIR improves body weight compared to diabetic rats and it indicates preventive effect of EESIR on degradation of structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of body weight after administration of STZ may be due to the loss of degradation of structural proteins [32]. The administration of EESIR improves body weight compared to diabetic rats and it indicates preventive effect of EESIR on degradation of structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a cluster form of diseases symbolized by abnormal high blood sugar and an elevated risk of complications from vascular diseases (Davis & Granner, ). The metabolic and endocrine disorders take place due to impaired insulin action and or secretion (Veeramani, Pushpavalli, & Pugalendi, ). Currently, there are 382 million people affected by diabetes worldwide and assumed to increase to 592 million by the year 2035 (Gandhi & Wareham, ).…”
Section: Introductionmentioning
confidence: 99%
“…No signs of retinopathy were observed in rats treated with zinc-insulin or chitosan-zinc-insulin containing formulations indicated that the released insulin helped in preventing the onset of diabetes related microvascular complications. It has been reported that STZ induced diabetes causes reduction in body weight due to the loss/degradation of structural proteins, which mainly contribute to the body weight [47]. Thus, after STZ treatment, a significant and drastic weight loss was observed in all groups.…”
Section: Discussionmentioning
confidence: 87%